Change People Demands to Policies: The Roles of Elected Representatives - Brahim, Malike; Mohamad, Musliza (2017)
The people have various demands to the government. The demands are different according to different groups in wanting to obtain money, medicine, housing, subsidies. safeguard and other reIated necessities and requirements. The demands channeled to government through the elected representatives. However, not all demands will fulfill but need to evaluate based on priorities by the government before it is changed into public policies. This paper offer an analysis of the demands From people divided into eight priorities such as educational, housing, agricultul, animal husbandry, safety, facilities, religious issues and households. The demands are an input that processed by the government and produced as aids, projects, programs and plans that organized by the federal or state agencies. After policies implemented, the people gives their feedback as outcomes into the policies implemented either they satisfy or otherwise. Therefore, the Malaysian government introduced various policies for people convenience.